2011
DOI: 10.1590/s0004-282x2011000500013
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making impairment in obsessive-compulsive disorder as measured by the Iowa Gambling Task

Abstract: Objective: This study aims to evaluate the process of decision-making in patients with obsessive-compulsive disorder (OCD) using the Iowa Gambling Task (IGT). In addition, we intend to expand the understanding of clinical and demographic characteristics that influence decision-making. Method: Our sample consisted of 214 subjects (107 diagnosed with OCD and 107 healthy controls) who were evaluated on their clinical, demographic and neuropsychological features. Moreover, the Iowa Gambling Task (IGT), a task that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 33 publications
11
52
0
1
Order By: Relevance
“…In accordance with the functional alteration of orbitofrontal-striatal circuits, previous studies have frequently demonstrated reduced IGT score in patients with OCD (Cavedini et al, 2002(Cavedini et al, , 2012(Cavedini et al, , 2010da Rocha et al, 2011a;Kashyap et al, 2013;Starcke et al, 2009Starcke et al, , 2010. On the other hand, two studies reported impaired performance in only subgroups of patients with OCD (Lawrence et al, 2006;Nielen et al, 2002), and one study revealed comparable performance in medication-naïve patients with OCD (Krishna et al, 2011).…”
Section: Introductionmentioning
confidence: 58%
“…In accordance with the functional alteration of orbitofrontal-striatal circuits, previous studies have frequently demonstrated reduced IGT score in patients with OCD (Cavedini et al, 2002(Cavedini et al, , 2012(Cavedini et al, , 2010da Rocha et al, 2011a;Kashyap et al, 2013;Starcke et al, 2009Starcke et al, , 2010. On the other hand, two studies reported impaired performance in only subgroups of patients with OCD (Lawrence et al, 2006;Nielen et al, 2002), and one study revealed comparable performance in medication-naïve patients with OCD (Krishna et al, 2011).…”
Section: Introductionmentioning
confidence: 58%
“…The respondents have to select the best option based in a four-point Likert type-scale to describe the frequency of certain behaviors and situations linked with impulsivity. The BIS-11 has three subscales: attentional impulsivity (items 6,5,9,11,20,24,26,28), motor impulsivity (items 2,3,4,16,17,19,21,22,23,25,30) and non-planning impulsivity (items 1,7,8,10,12,13,14,15,18,27,29). Furthermore, the BIS-11 has a total score ranges from 30 to 120 points.…”
Section: Barratt Impulsiveness Scale -Eleventh Edition Brazilian Vermentioning
confidence: 99%
“…Several psychopathologies are associated with impairments in EF processes, such as Attention Deficit Hyperactivity Disorder (ADHD) 6 , Bipolar Disorder 7 , Obsessive Compulsive Disorder 8 , and Schizophrenia 9 . In clinical samples, as in ADHD, EF deficits are related to poor functional outcomes, such as educational fields 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Some other outcome measures used in this regard include total money won [38], total of cards selected on individual decks [29], comparison between the number of cards selected from the decks A and C (lowfrequency loses) and decks B and D (high-frequency loses) [29], and analysis of selections in the later trials versus the earlier ones [30,37]. This issue motivated us to compare the normalized number of good bets in the first-300 versus the last-100 trials.…”
Section: Discussionmentioning
confidence: 99%
“…This measure was calculated within four quartile time bins to show subjects' learning trends over trials. We also explored the behavioral performance by using the total number of good bets as in previous studies [29,30]. Finally, we computed a metric of participants' tendency to re-engage with a previous bet despite a negative/positive outcome.…”
Section: Behavioral Analysismentioning
confidence: 99%